Acculturation through Code-Switching Linguistic Analysis in Three Short-Stories: “Invierno”, “Nilda” and “The Pura Principle” (Díaz 2012) - Sánchez, María Jesús; Pérez-García, Elisa (Miscelánea: A Journal of English and American Studies, 2020)
The purpose of this article is to investigate whether Yunior, a character and narrator in the three short stories under study, “Invierno”, “The Pura Principle”, and “Nilda”, becomes absorbed into American culture or obtains a positive relationship with this culture without losing his Dominican identity. Quantitative analyses of the vocabulary in the L1 code-switches (Spanish) and of the L2 (English) vocabulary used by Yunior in the stories were carried out to appraise his linguistic progression. Code-switching was analyzed because it gives insights into how situation and context influences language use and why the characters use the language they do. The results obtained, by means of three common lexical measures used in foreign language research (lexical density, age of acquisition and lexical sophistication), allowed us to assess Yunior’s change of identity. According to the acculturation model, Yunior becomes acculturated in the host country, showing progression and integration with many cultural aspects of American life and the English language due to his formal education and early age of acquisition of L2.
Keywords: Code-switching; Identity; Acculturation; Lexical density; Age of acquisition